The Method of Aby Al Barakat AlANBARI IN HIS BOOK “manthoor Al Fawaed” - Ismail, Malak (Dirasat: Human and Social Sciences, 2019)
This is a research about the method of Aby Al Barakat Al Anbari in his book Manthoor Al Fawaed. This book focuses on the characteristics of the book in general, different methodologies and the importance of the book. The research concludes that the books benefit is limited